Combustion Performance Comparison of Charcoal and Coconut Shell Charcoal Briquettes for Renewable Energy Applications - Suryaman; Kiki Zakaria; Nurfadhlina Abdul Halim (International Journal of Ethno-Sciences and Education Research, 2026)
The increasing demand for renewable energy has encouraged the utilization of biomass-based solid fuels derived from agricultural waste. This study experimentally compares the combustion performance of coconut shell charcoal and coconut shell charcoal briquettes under controlled laboratory conditions. The evaluation focused on combustion temperature characteristics, burning rate, effective burning duration, and thermal efficiency using the Water Boiling Test (WBT) method. The results indicate that coconut shell charcoal achieved a higher peak combustion temperature of approximately 720 °C and a higher burning rate of 9.6 g/min, reflecting rapid and intense heat release. In contrast, charcoal briquettes exhibited a more stable combustion behavior with a longer effective burning duration of about 78 minutes compared to 42 minutes for charcoal, and a higher thermal efficiency of 31.4%, while charcoal reached 23.6%. These differences are mainly attributed to variations in bulk density, porosity, and combustion kinetics between the two fuel forms. Overall, coconut shell charcoal is more suitable for applications requiring rapid heat generation, whereas charcoal briquettes offer superior performance in terms of fuel efficiency, combustion stability, and sustained heat output, making them a more favorable option for renewable and efficient biomass energy applications.